Gold-catalyzed cycloadditions of allenes via metal carbenes. Issue 25 (5th June 2022) - Gao, Guang-Qin; Ma, Guang; Jiang, Xiao-Lei; Liu, Qing; Fan, Cai-Ling; Lv, Dong-Can; Su, Hui; Ru, Guang-Xin; Shen, Wen-Bo
Abstract : This review will focus on gold-catalyzed cycloadditions of allenes as efficient methods of assembling functionalized cyclic molecules via gold carbenes. Abstract : In recent years, gold-catalyzed cycloadditions of allenes, especially those involving a gold carbene intermediate, have received significant interest, as they avoid the utilization of potentially hazardous and inaccessible diazo compounds as starting materials for carbene generation. Cycloaddition reactions consisting of the uncomplicated addition of two or more unsaturated functional groups are one of the most efficient synthetic methodologies for the rapid assembly of carbo- and heterocyclic structures from simple acyclic precursors. In this review, we introduce an overview of the advances in the gold-catalyzed cycloaddition of allenes via a metal carbene intermediate and categorize these reactions according to the reaction types of the cycloadditions.